New Regional Definition and Spatial Analysis of Regional Inequalities in Turkey. Related to the Regional Policies of EU - Ferhan Gezýcý (European Regional Science Association (ERSA), 2004)
Increasing interest on regional inequalities can be easily observed not only within countries but also among countries, related to globalization process and trade unions. European Union has also focused on issues on regional development, inequalities and convergence. Enlargement of EU makes this issue very significant, in terms of structural funds allocation and integration. In this context, Turkey has also several projects for adjustment. One of them is defining NUTS regions in order to adjust regions to EU norms and create some comparable statistical data. In this paper, it is examined regional inequalities in Turkey for NUTS regions, following two other papers (Gezici&Hewings, 2001; 2003) which are examined regional inequalities in terms of three different regional classification. Thus, this paper will give additional information to make a comparison between different regional classifications. Moreover, it will give an opportunity to evaluate adjustment process related to regional issues in Turkey. Regional inequalities will be identified using spatial data analysis in order to see the effects of spatial dependence on regional inequalities. Key words: interregional inequalities, spatial data analysis, NUTS regions, Turkey
Keywords: 330; interregional inequalities; spatial data analysis; NUTS regions; Turkey